Synergy of Nano Silica and Anionic Surfactant Fluid as Chemical Enhanced Oil Recovery - Rowi, Khasan; Subagio, Agus; Ngadiwiyana; Taufiq, Heydar Ruffa; Azis, Muhammad Mufti; Prasetiyo, Bayu Dedi; Sitompul, Victor; Paryoto, Sumadi; Winata, Denie Tirta; Diharja, Tino; Yutaka, Michael Arya; Syarifudin, Abimanyu Putra; Firmansyah, Wahyu; Koestono, Hary (Scientific Contributions Oil and Gas, 2025)
Silica nanofluids attract significant attention for enhanced oil recovery (EOR) applications due to their ability to alter rock wettability. However, silica nanofluids exhibit limitations in thermal stability. The addition of anionic surfactants aims to overcome these limitations. The synergisticAnionic surfactants are added to address the thermal stability issues of silica nanofluids. The synergy interaction between silica nanoparticles (SNPs) and anionic surfactants enhances  wettability alteration, reduces interfacial tension (IFT), improves thermal stability, and increasing oil recovery. This study investigates the synergistic effects of SNPs, alpha olefin sulfonate (AOS) surfactant, and disodium laureth sulfosuccinate (DLS) co-surfactant in nanofluid formulations applied to sandstone reservoirs. Laboratory experiments employ colloidal nano silica with two particle sizes, 8 nm (SNP-01) and 3 nm (SNP-02), combined with AOS-DLS anionic surfactants at various concentrations . The study showed that the silica nanofluid remains stable for up to 3 months at temperatures below 80°C for both SNP types at a concentration of 0.1% with surfactant concentrations 0.3% AOS and 0.3% DLS in  3% brine solution. The addition of SNPs decreases the contact angle, whereas surfactants do not significantly affect the contact angle; however, surfactant effectively reduce the IFT, while  nano silica shows minimal influence on IFT values. Core flooding analysis showed that the SNP-02 nanofluid produced the highest recovery factor of 12.1% OOIP. Futhermore, SEM analysis showed that silica nanofluid injection removes surfactant impurities and enhances rock porosity.